2021
DOI: 10.1099/jgv.0.001616
|View full text |Cite
|
Sign up to set email alerts
|

Type I interferon receptor-independent interferon-α induction upon infection with a variety of negative-strand RNA viruses

Abstract: Type I interferons (IFNs) are a first line of defence against viral infections. Upon infection, a first small wave of early type I IFN, mainly IFN-β and particularly IFN-α4, are induced and bind to the type I IFN receptor (IFNAR) to amplify the IFN response. It was shown for several viruses that robust type I IFN responses require this positive feedback loop via the IFNAR. Recently, we showed that infection of IFNAR knockout mice with the orthomyxovirus Thogoto virus lacking the ML open reading frame (THOV(ML-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 86 publications
(142 reference statements)
0
1
0
Order By: Relevance
“…As shown before (7), IFNAR -/mice succumb to infection with RVFV cl13, which is accompanied by body weight loss and a drop in body temperature, while their WT counterparts survive the infection and do not show such symptoms (Figures 1A-C). In line with this, WT mice mount IFN-a responses 12 hpi while IFNAR -/mice produced high amounts of IFN-a (up to ~4500 pg/ml) at 30 hpi indicating uncontrolled IFN-a production in the course of infection (Supplementary Figure 1).…”
Section: Ifnar -/Mice Develop Severe Liver Damage Upon Infection With...supporting
confidence: 68%
See 3 more Smart Citations
“…As shown before (7), IFNAR -/mice succumb to infection with RVFV cl13, which is accompanied by body weight loss and a drop in body temperature, while their WT counterparts survive the infection and do not show such symptoms (Figures 1A-C). In line with this, WT mice mount IFN-a responses 12 hpi while IFNAR -/mice produced high amounts of IFN-a (up to ~4500 pg/ml) at 30 hpi indicating uncontrolled IFN-a production in the course of infection (Supplementary Figure 1).…”
Section: Ifnar -/Mice Develop Severe Liver Damage Upon Infection With...supporting
confidence: 68%
“…CD4Cre IFNAR flox/flox and CD19Cre IFNAR flox/flox mice (37), LysMCre IFNARflox/flox mice (38), and CD11cCre IFNARflox/flox (6) have been described before. To obtain MyD88 -/-IFNAR -/double-deficient mice and MAVS -/-IFNAR -/double-deficient mice, MyD88 -/mice or MAVS -/mice were intercrossed with IFNAR -/mice as described before (7). All mice were bred under specific pathogen free conditions at the Zentrale Tierhaltung of the Paul-Ehrlich-Institut.…”
Section: Micementioning
confidence: 99%
See 2 more Smart Citations
“…Besides, the activation of TLR2, the major TLR involved in the recognition of M. ulcerans vesicles [11], has been previously shown to induce the expression of type-I interferons as well [38]. Also, another study has shown that the IFNAR feedback loop is not strictly necessary for robust type I IFN expression in the context of viral infection [44]. We therefore hypothesized that either the first wave of IFN-β or ISGs induced in an IFNAR pathway-independent manner may promote macrophage tolerance to M. ulcerans despite the presence of mycolactone.…”
Section: Discussionmentioning
confidence: 99%